International experience of using report forms for hospital-based health technology asssessment - О. M. Filiniuk; М. М. Babenko (The State Expert Center of the Ministry of Health of Ukraine, 2023)
Hospital-based health technology assessment (HB-HTA) is one of the components of public management and support hospital managers to science-based decision-making regarding the implementation of new and innovative health technologies (HT). HB-HTA includes the processes and methods used to make HTA reports in and for hospitals. Ukraine has already started implementing hospital-based HTA, but a number of steps are still needed to fully implement HTA at the hospitals. One of them is the choice of HB-HTA report form, which will be appropriate to use in the practical activities of hospitals in Ukraine. The purpose of the study is to analyse the international experience of using different HB-HTA report form with the aim of selecting the optimal HB-HTA report form for hospitals in Ukraine. There were analysed different forms of HTA reports in Ukraine regulatory framework, international scientific literature, the AdHopHTA handbook, which included the following countries: Norway, Finland, Turkey, Spain, Austria, Italy, Estonia, Denmark, Switzerland, in international HTA database INAHTA, Canadian and Kazakhstan report databases. The methods of content analysis, systematization and generalization were used. Making managerial decisions about investment or disinvestment in health technology requires information that meets the hospital stakeholders needs. Such scientifically based information is provided by HB-HTA report form. There are a wide range of HB-HTA reports forms in terms of content, subject matter, structure and resources (time and staff). Each is based on the EUnetHTA HTA core model. For introducing a hospital-based HTA, the countries of the world most often choose the mini-HTA form. Mini-HTA supports hospital managers to make science-based strategic decisions of the introduction of new treatment methods, new indications for the use of existing technology, medical equipment, medical devices, or stopping the usage of health technology. The choice between performing a mini-HTA or a more comprehensive hospital-based HTA often requires a balance between the quality and thoroughness and the necessary speed of assessment in a specific situation. From the authors' point of view, the most applicable to Ukrainian context is the mini-HTA form. Adapting mini-HTA and approving it as a recommended report form at the state level will provide an opportunity to more widely HTA usage by hospitals in Ukraine.